Mobile Payment and Informal Business: Evidence from China's Household Panel Data - Wang, Xue (China & world economy, 2020)
This paper uses household panel data to explore the impact of mobile payments on China's household business activity. Using a difference‐in‐difference fixed effect specification, I find that mobile payment users are more likely to operate small‐scale and self‐employed informal businesses. The impact of using mobile payment primarily derives from the transition of agricultural families to business owners and the development of informal businesses. The paper illustrates an associated increase in employment and income for family members, with more pronounced effects on low‐income and rural households. It also provides prima facie evidence of the increase in fund transfers, which is important for risk sharing that informal businesses may encounter.